Closing the gaps: Maori and information literacy - Lilley, Spencer C (Massey University, 2008)
This paper focuses on the reasons why information literacy is a concept that has yet to make an impact on Maori. Although Maori participation as librarians and library users has increased dramatically over the last decade there are still a range of barriers that continue to inhibit access to library and information services for Maori. The relevance of these barriers to the 'information literacy divide' are analysed and actions are identified which will allow a strategy to be created to close the gap.
Paper presented at User Education for User Empowerment: Commonwealth Library Association Conference 19 – 20 October 2000 Christchurch, New Zealand.
Keywords: Librarianship; Maori; Fields of Research::330000 Education